Rational Design, Synthesis, and Evaluation of Tetrahydroxamic Acid Chelators for Stable Complexation of Zirconium(IV). Issue 19 (16th April 2014) - Guérard, François; Lee, Yong‐Sok; Brechbiel, Martin W.
Abstract Metals of interest for biomedical applications often need to be complexed and associated in a stable manner with a targeting agent before use. Whereas the fundamentals of most transition‐metal complexation processes have been thoroughly studied, the complexation of ZrIV has been somewhat neglected. This metal has received growing attention in recent years, especially in nuclear medicine, with the use of 89Zr, which a β+‐emitter with near ideal characteristics for cancer imaging. However, the best chelating agent known for this radionuclide is the trishydroxamate desferrioxamine B (DFB), the ZrIV complex of which exhibits suboptimal stability, resulting in the progressive release of 89Zr in vivo. Based on a recent report demonstrating the higher thermodynamic stability of the tetrahydroxamate complexes of ZrIV compared with the trishydroxamate complexes analogues to DFB, we designed a series of tetrahydroxamic acids of varying geometries for improved complexation of this metal. Three macrocycles differing in their cavity size (28 to 36‐membered rings) were synthesized by using a ring‐closing metathesis strategy, as well as their acyclic analogues. A solution study with 89Zr showed the complexation to be more effective with increasing cavity size. Evaluation of the kinetic inertness of these new complexes in ethylenediaminetetraacetic acid (EDTA) solution showed significantly improved stabilities of the larger chelates compared with 89Zr‐DFB, whereas the smaller complexes suffered from insufficient stabilities. These results were rationalized by a quantum chemical study. The lower stability of the smaller chelates was attributed to ring strain, whereas the better stability of the larger cyclic complexes was explained by the macrocyclic effect and by the structural rigidity. Overall, these new chelating agents open new perspectives for the safe and efficient use of 89Zr in nuclear imaging, with the best chelators providing dramatically improved stabilities compared with the reference DFB.